Phosphorylation of multifunctional nucleolar protein nucleophosmin (NPM1) by aurora kinase B is critical for mitotic progression. Issue 14 (21st May 2014) - Shandilya, Jayasha; Senapati, Parijat; Dhanasekaran, Karthigeyan; Bangalore, Suma S.; Kumar, Manoj; Hari Kishore, A.; Bhat, Akshay; Kodaganur, Gopinath S.; Kundu, Tapas K.
Abstract : The functional association of NPM1 with Aurora kinases is well documented. Surprisingly, although NPM1 is a well characterized phosphoprotein, it is unknown whether it is a substrate of Aurora kinases. We have found that Aurora kinases A and B can phosphorylate NPM1 at a single serine residue, Ser125, in vitro and in vivo. Phosphorylated‐S125‐NPM1 (pS125‐NPM1) localizes to the midbody region during late cytokinesis where it colocalizes with Aurora B. The overexpression of mutant (S125A) NPM1 resulted in the deregulation of centrosome duplication and mitotic defects possibly due to cytokinesis failure. These data suggest that Aurora kinase B‐mediated phosphorylation of NPM1 plays a critical role during mitosis, which could have wider implications in oncogenesis. Abstract : NPM1 and Aurora Kinases play important roles in mitosis. NPM1 is phosphorylated by Aurora Kinase B predominantly at Ser125 during mitosis. Ser125‐phosphorylated NPM1 localizes in the midbody region during cytokinesis. Ser125‐phosphorylated NPM1 levels are high in oral tumor tissues. Aurora Kinase B along with NPM1 overexpression may facilitate oncogenesis.